Addressing the development implications of illicit economies: The rise of a policy and research agenda - Allan Gillies; John Collins; Alexander Soderholm (Journal of Illicit Economies and Development (JIED), 2019)
This special issue of the Journal of Illicit Economies and Development builds on a growing, multifaceted research and policy agenda that advances development perspectives of illicit economies in the Global South. Conventional policy discourses have typically framed this issue as a security problem, drawing direct and often simplistic causalities with underdevelopment. Illicit economies frequently drive violence, corruption, exploitation and failures in governance, for example. However, for many communities living in poverty and conflict-affected areas across the globe, involvement in illicit economic activity can also ameliorate the immediate problems they face. Illicit economies may provide vital sources of livelihood and underpin stable political orders and socio-economic development at the margins of the state. Broad, securitised policy responses may cause more harm than good in such contexts. Scoping the complex relationship between illicit economies and development, this introductory article outlines key themes of the special issue.
Keywords: 330; illicit economies; JIED; development; livelihoods; corruption; governance